ELEVATED SYSTOLIC BLOOD PRESSURE AT MIDDLE-AGE REMAINS A SIGNIFICANT CARDIOVASCULAR RISK FACTOR THROUGHOUT LIFE. (June 2018) - Engeseth, K.; Prestgaard, E.E.; Grundvold, I.; Liestol, K.; Mariampillai, J.E.; Kjeldsen, S.E.; Bodegard, J.; Erikssen, J.E.; Gjesdal, K.; Skretteberg, P.T.
Abstract : Objective: Systolic blood pressure, prevalence of smoking, family history of coronary heart disease, cholesterol and cardiorespiratory fitness are well established as cardiovascular risk factors. In the present study we aimed to investigate how one measurement these variables at middle-age influenced risk of cardiovascular death during the first, intermediate and late part of a 35-year observation period, respectively. Figure. No caption available. Design and method: Systolic blood pressure, prevalence of smoking, family history of coronary heart disease, cholesterol and cardiorespiratory fitness were measured in 2014 apparently healthy, middle-aged Caucasian men by clinical examination, blood tests and an ECG-monitored, symptom-limited bicycle test. End points were registered after 35 years in a nationwide scrutiny of charts in all hospitals, and from the national Cause of Death registry. Early cardiovascular death was defined as event before 12 years of observation, intermediate event between 12 and 23 years of observation and late event between 23 and 35 years of observation. Impact of predictors and relative risks were estimated using Cox proportional hazards models. When estimating risks of intermediate and late cardiovascular death, men who died within 12 and 23 years were excluded. Results: We found 80 events of early, 207 events of intermediate and 241 events of late cardiovascular death. Age, systolic blood pressure, smoking status, and cholesterol were significant predictors of early, intermediate and late cardiovascular death. Baseline physical fitness was a significant and independent predictor of early and a borderline significant predictor of intermediate cardiovascular death but had no predictive impact on late cardiovascular death. Family history of coronary heart disease was a significant and independent predictor of early and intermediate, but not late cardiovascular death (Table1). Conclusions: Systolic blood pressure, smoking, and cholesterol measured at a median age 49 years were strong predictors of early, intermediate and late cardiovascular death during 35 years. Physical fitness at middle age and family history of coronary heart disease were only associated with risk of cardiovascular death before reaching 72 years. Risk factors for CV death have different persistence throughout life and systolic blood pressure at middle-age remains a significant cardiovascular risk factor until old ages.